The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1123/jpah.7.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Step Counts of 10- to 11-Year-Old Children by Ethnicity and Metropolitan Status

Abstract: Background:The purpose of this study was to conduct a secondary analysis by combining 2 pedometer data sets to describe and analyze pedometer-determined steps/day of children by ethnicity and metropolitan status. Methods: Participants were 582 children (309 girls, 273 boys; 53% Hispanic, 26% Caucasian, 21% African American) age 10 to 11 years (M = 10.37 ± 0.48) attending 1 of 10 schools located in urban, suburban, and rural settings. Participants wore a research grade pedometer for at least 3 week/school days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Other categorisation variables commonly applied where appropriate include age group or school year/grade and BMI since it has been reported that step counts decline with increasing age 39,46,52,75 and BMI. 50,63 Ethnic differences in step counts have also been reported, 47 therefore where relevant it may also be important to report step count data according to ethnicity.…”
Section: Methods Of Data Treatment Analysis and Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other categorisation variables commonly applied where appropriate include age group or school year/grade and BMI since it has been reported that step counts decline with increasing age 39,46,52,75 and BMI. 50,63 Ethnic differences in step counts have also been reported, 47 therefore where relevant it may also be important to report step count data according to ethnicity.…”
Section: Methods Of Data Treatment Analysis and Reportingmentioning
confidence: 99%
“…A number of researchers have excluded data from a particular day, or all of the data from a participant, if participants have reported removing the pedometer for over an hour. 11,[39][40][41][42][43][44][45][46][47][48][49][50] To enhance comparability between studies it is recommended that future studies apply the same protocol of excluding data from a particular day if participants report removing the pedometer for over one hour on that day.…”
Section: Pedometer Wear Timementioning
confidence: 99%
“…(37, 41) Compared to the general youth population, lower percentages of disadvantaged and urban youth appear to be meeting the recommendations. (8, 15, 16, 19) The known health benefits of physical activity support prioritizing the identification and characterization of these and other subgroups at high risk for inactivity. In addition, the recent Surgeon General’s Call to Action, titled, “Step it up!”(38), highlighted the need to identify factors related to PA levels in these subgroups that may better inform targeted PA intervention efforts for those most in need of improvement.…”
Section: Introductionmentioning
confidence: 99%
“…(36) Aspects of the built environment that vary across metropolitan settings have also emerged as factors that may lead to differences in PA levels across subgroups. (8, 16). In relation to this, one study reported that urban youth had significantly lower average (stdev) step counts/day compared to suburban and rural youth (10,856 ± 3,706 versus 12,297 ± 3,616 and 11,934 ± 3,374, P<0.05); with the lowest mean step counts/day in urban females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation